2021
DOI: 10.1038/s41467-021-26965-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo volumetric imaging of calcium and glutamate activity at synapses with high spatiotemporal resolution

Abstract: Studying neuronal activity at synapses requires high spatiotemporal resolution. For high spatial resolution in vivo imaging at depth, adaptive optics (AO) is required to correct sample-induced aberrations. To improve temporal resolution, Bessel focus has been combined with two-photon fluorescence microscopy (2PFM) for fast volumetric imaging at subcellular lateral resolution. To achieve both high-spatial and high-temporal resolution at depth, we develop an efficient AO method that corrects the distorted wavefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…S6). Previous investigation by us indicated that Bessel foci are degraded by Zernike aberration modes with |m| > 1 (e.g., astigmatism and trefoil) (24). In contrast, astigmatism and trefoil degraded Bessel-droplet PSFs much less than Bessel PSFs in simulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S6). Previous investigation by us indicated that Bessel foci are degraded by Zernike aberration modes with |m| > 1 (e.g., astigmatism and trefoil) (24). In contrast, astigmatism and trefoil degraded Bessel-droplet PSFs much less than Bessel PSFs in simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Z r with |m| > 1 (e.g., astigmatism and trefoil) (24). In contrast, astigmatism and trefoil degraded Bessel-droplet PSFs much less than Bessel PSFs in simulation.…”
Section: Experimental Characterization Of Bessel-droplet Focimentioning
confidence: 89%
See 3 more Smart Citations